Study on the Dynamics and Ecological Impact of Lamprey Populations Based on Growth Indicators and Mathematical Models - Luo, Kaiwen; Jiang, Hengyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
This study explores the growth and population dynamics of lampreys, focusing on the relationship between growth rate, sex ratio, and interspecific interactions. Utilizing the Von Bertalanffy growth equation, we establish a non-monotonic growth rate function and an asymmetrical S-shaped weight gain curve for lampreys. Population distribution analysis reveals a normal distribution for mass and age, with a joint probability density function for coupled distributions. The study delves into the impact of sex ratio on growth rate and reproductive strategies, highlighting that slow-growing individuals are more likely to become male in resource-limited environments. The Lotka-Volterra Equation is employed to examine interspecific relationships, revealing distinct roles for males and females in predation, competition, and mutualistic symbiosis. Our findings suggest that sex ratios significantly influence population dynamics, with implications for understanding lamprey ecology and managing their populations in aquatic ecosystems.